Preliminary analysis of Malaysian Corpus of Financial English (MaCFE) - Roslan Sadjirin,; Roslina Abdul Aziz,; Norzie Diana Baharum,; Noli Maishara Nordin,; Mohd Rozaidi Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper presents the findings of the preliminary analysis conducted on the Malaysian Corpus of Financial English (MaCFE). MaCFE is a specialised corpus consisting of written documents compiled from banks in Malaysia and the corpus is currently housing approximately 4.3 million word tokens. The aim of the analysis was to evaluate the suitability of the texts chosen to represent the financial domain. The preliminary analysis involved generating the word list and lists of co-occurrences from MaCFE. RapidMiner Studio Educational 7.5.001 and an in-house Java programming solution was utilised to perform the analysis. The word list and lists of 50 most frequent two-word and three-word co-occurrences generated from the analysis reveal that the text compilation is representative of the financial domain in Malaysia. The study concludes by discussing the pedagogical implications of the findings.